Alternative ranking method in Dynamic Data Envelopment Analysis (DDEA) - Mahnaz Maghbouli; Omid Yaghbubi agreh; Zahra Mohammadnezhad (Iranian Journal of Optimization, 2015)
The motivation of this paper is to propose such equitable method for ranking all decision making units (DMUs) in dynamic Data Envelopment Analysis (DDEA) framework. As far as we are aware there is not more studies in dynamic DEA literature. What's more, in such cases the best operating unit is important to be sampled for the others in under evaluated time periods. However, in this special concept of DEA, quasi-fixed inputs or intermediate products are the source of inter temporal dependence between consecutive periods. Hence, in order to have suitable ranking for units operating in dynamic environment the minimum and maximum efficiency values of each DMU in dynamic state are computed. Also, we assume that the sum of efficiency values of all DMUs in dynamic state is equal to unity. Thereafter, the rank of each DMU is determined through the combination of its maximum and minimum efficiency values. A real case of Iranian gas companies highlights the applicability of the proposed method in Dynamic framework.